Studi Komparatif tentang Kemacetan Lalu Lintas Parah Komuter Jabodetabek: Bukti Empiris Survei 2019 dan 2023 - Linda Usfatul Hasanah; Chotib Chotib (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
Severe traffic congestion remains a persistent challenge in Greater Jakarta (Jabodetabek), driven in part by the imbalance between high private-vehicle use and low public-transport uptake. This study compares the incidence of severe congestion among commuters in 2019 and 2023 and examines changes in trip characteristics. We conduct descriptive analyses of microdata from the Jabodetabek Commuter Surveys (2019, 2023) using IBM SPSS 29.0.2.0(20), focusing on severe-congestion status, trip distance, travel time, and mode. Results show a decline in severe congestion in 2023 despite an increase in the number of commuters. Average trip distance decreased from ~21 km (2019) to ~10 km (2023), and travel time fell from ~60 minutes to ~31 minutes. These shifts are consistent with post-pandemic mobility changes-especially flexible/hybrid work—that shorten trip chains and redistribute demand. The study’s original contribution is a cross-year, microdata-based comparison for Jabodetabek that demonstrates congestion reductions are not solely attributable to roadway capacity increases but also to behavioral changes in mobility, a dimension rarely quantified in prior work. Practical implications include prioritizing suburban traffic management, strengthening multimodal integration for short-to-medium trips (integrated fares, timetable synchronization, improved last-mile services), and advancing behavioral policies to shift users toward public transport.